2022
DOI: 10.3389/fneur.2022.992416
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure, lateral sinus patency, and jugular ultrasound hemodynamics in patients with venous pulsatile tinnitus

Abstract: The clinical and hemodynamic characteristics of venous pulsatile tinnitus (PT) patients with normal or elevated cerebrospinal fluid pressure (CSFP) have not been clearly differentiated. This study aimed to explore CSFP among patients with PT as the solitary symptom, as well as quantitatively and qualitatively assess the role of the degree of transverse sinus (TS) stenosis and jugular hemodynamics in venous PT patients. A total of 50 subjects with venous PT with or without sigmoid sinus wall anomalies (SSWAs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Despite the strong correlation between PT and idiopathic intracranial hypertension (IIH) postulated by other studies (35)(36)(37)(38), most Asian patients do not meet the diagnostic criteria for definitive IIH and rarely exhibit associated symptoms. These symptoms are more likely related to body mass index (35).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the strong correlation between PT and idiopathic intracranial hypertension (IIH) postulated by other studies (35)(36)(37)(38), most Asian patients do not meet the diagnostic criteria for definitive IIH and rarely exhibit associated symptoms. These symptoms are more likely related to body mass index (35).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the strong correlation between PT and idiopathic intracranial hypertension (IIH) postulated by other studies (35)(36)(37)(38), most Asian patients do not meet the diagnostic criteria for definitive IIH and rarely exhibit associated symptoms. These symptoms are more likely related to body mass index (35). In this study, papilledema, with a prevalence of only 8%, is exclusively observed in the dehiscence group, all of whom experienced recent weight gain.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The bilateral sinus morphologic parameters measured in the 27 patients were the degree of TS stenosis, distance from the torcular herophili to the TS stenosis, and volume and length of the transverse-sigmoid sinus. TS stenosis was measured with Mimics software version 19.0 (Materialise, Leuven, Belgium) or the NUMARIS/4 workstation (SYNGO MR B17; Siemens AG, Munich, Germany) using patient-specific contrastenhanced two-dimensional time-of-flight MR slices (MR parameters are described in the reports by Guo and Wang 15 and Guo et al 16 ). After the TS measurements, volumetric and length measurements were recorded using 3-matic 11.0 (Materialise) based on three-dimensional computational models reconstructed using MR venograms.…”
Section: Measurement Of Ts Stenosis and Bilateral Transverse-sigmoid ...mentioning
confidence: 99%
“…15 According to the Monro-Kellie doctrine, the combined volume of the brain, cerebrospinal fluid (CSF), and intracranial arterial/ venous compartments is kept constant. 16 Iatrogenically increased ICP is caused by severe blockage of the transverse-sigmoid sinus on the ipsilateral side and poor collateral sinus flow on the contralateral side, leading to a restriction in the volume of outflow from the venous compartment. 16,17 Operating on the venous sinus wall can be risky when surgeons disregard or are unaware of the pattern of the bilateral transverse-sigmoid sinuses, which are important conduits for the cerebral venous return of the posterior fossa.…”
Section: Introductionmentioning
confidence: 99%